Parental mental health and risk of poor mental health and death by suicide in offspring - Maguire, Aideen; Tseliou, Foteini; O'Reilly, Dermot (International Journal of Population Data Science, 2018)
Background Suicide is a major public health concern. Identifying those most at risk is vital for effective targeting of interventions. Mental health (MH) has a genetic component and parental MH is associated with child’s MH. However, little is known on the effect of parental MH on a child’s risk of death by suicide. Methods Data from 2011 Northern Ireland Census was linked to 5 years’ death records (2011-2015) to construct multi-level regression models to determine if children living with parents with poor self-rated MH are at an increased risk of poor MH themselves and an increased risk of death by suicide. Results 618,970 individuals live with their parents; with almost 1 in 7 (13.7%) living with parents with poor MH and 225 (0.1%) dying by suicide during follow-up. Interim results suggest after full adjustment, children with 2 parents with poor MH were 5 times more likely to have poor MH themselves (OR=5.30, 95% CI 4.62,6.09), and children with 1 parent with poor MH were 67% more likely to die by suicide compared to children of parents with good MH (OR=1.67, 95%CI 1.19, 2.33). Conclusions Parental MH is associated with child suicide risk even after adjustment for their own MH status.